2020
DOI: 10.1007/s42399-020-00627-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated D-Dimer Is Associated with Multiple Clinical Outcomes in Hospitalized Covid-19 Patients: a Retrospective Cohort Study

Abstract: D-dimer is a prognostic marker for Covid-19 disease mortality and severity in hospitalized patients; however, little is known about the association between D-dimer and other clinical outcomes. The aim of this paper was to define a threshold of D-dimer to use in hospitalized patients with Covid-19 and to assess its utility in prognosticating in-hospital mortality, development of an acute kidney injury (AKI), and need for hemodialysis, vasopressors, or intubation. This is a single-center, retrospective, cohort r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Our ICU admission and mortality rate of patients with AKI are similar to previous studies (9)(10)(11)(12)(13)(14)(15). We found that the severity of AKI among patients with CA-AKI was similar to patients with HA-AKI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our ICU admission and mortality rate of patients with AKI are similar to previous studies (9)(10)(11)(12)(13)(14)(15). We found that the severity of AKI among patients with CA-AKI was similar to patients with HA-AKI.…”
Section: Discussionsupporting
confidence: 89%
“…Coronavirus disease 2019 (COVID-19) (1, 2) caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) is the worst public health disaster of the century, accounting for millions of infections and deaths globally. Hospital-acquired acute kidney injury (HA-AKI) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) is a frequent complication of COVID-19 that is associated with critical illness and increased mortality. Proposed mechanisms of AKI in patients with COVID-19 include volume depletion, hypotension, sepsis, cytokine storm, and direct viral-induced AKI, although the latter has not been proven (16).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, d -dimer concentration, an indicator of blood clots [ 44 ], elevated − 1 day prior but peaked a day later than Cr concentration, suggesting that potential embolic event might be present early but peaked in the later stage [ 10 ]. d -Dimer has been reported to be associated with COVID-19 and high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it should be noted that the differences between results of external validation were negative by more than 20% and the statistical significance below 10% suggests that they may become significant should the sample size be increased to enable a more extensive external validation. Fourth, in our study, only the prognostic role of D-dimer levels upon admission was explored; some studies have reported a high ability of D-dimer peak during hospital stay for prediction of multiple outcomes [ 41 ]. We also did not analyze the potential role of serial D-dimer levels to distinguish severe COVID-19 cases from the mild/moderate forms [ 42 ].…”
Section: Discussionmentioning
confidence: 99%